On the Applications of a New Technique to Solve Linear Differential Equations, with and without Source - Gurappa, N.; Jha, P.K.; Panigrahi, P.K. (Symmetry, Integrability and Geometry: Methods and Applications, 2007)
A general method for solving linear differential equations of arbitrary order, is used to arrive at new representations for the solutions of the known differential equations, both without and with a source term. A new quasi-solvable potential has also been constructed taking recourse to the above method.